1987
DOI: 10.1113/jphysiol.1987.sp016820
|View full text |Cite
|
Sign up to set email alerts
|

The effects of noradrenaline on neurones in the rat dorsal motor nucleus of the vagus, in vitro.

Abstract: SUMMARY1. Intracellular recordings were made from vagal motoneurones identified by antidromic stimulation in the dorsal motor nucleus of the vagus (d.m.v.) in slice preparations of rat medulla oblongata.2. Noradrenaline (NA) applied by perfusion (0O01 /IM to 1 mM) depolarized 55%, hyperpolarized 32 % and produced a biphasic response (hyperpolarization followed by depolarization) in 9% of the d.m.v. neurones tested.3. The NA effects persisted after complete elimination of synaptic inputs during perfusion with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
53
0
2

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 32 publications
7
53
0
2
Order By: Relevance
“…Anatomic studies have shown that the DMV receives massive projections from the NST (Rogers, Kita, Butcher & Novin, 1980). Since the synaptic inputs from the NST to the DMV were considered to be preserved in the slice preparations (Fukuda et al 1987), the transsynaptic effects of All on the DMV neurones mav be mediated bv its action on the neurones in the NST. However, involvement of interneurones within the DMV that have All receptors cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anatomic studies have shown that the DMV receives massive projections from the NST (Rogers, Kita, Butcher & Novin, 1980). Since the synaptic inputs from the NST to the DMV were considered to be preserved in the slice preparations (Fukuda et al 1987), the transsynaptic effects of All on the DMV neurones mav be mediated bv its action on the neurones in the NST. However, involvement of interneurones within the DMV that have All receptors cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…9). However, DMV neurones were excited by noradrenaline through a1-receptors (Fukuda et al 1987). In addition, it has been generally accepted that a1-adrenergic activation induces inositol phospholipid breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Although a weak partial cu2-adrenergic agonist (Medgett et al, 1978) clonidine is remarkably effective in mimicking noradrenergic inhibition in several different regions in the nervous system, including the LC (Cedarbaum and Aghajanian, 1977;Reiner, 1985;Williams et al, 1985) the rat sympathetic ganglion (Brown and Caufield, 1979), substantia gelatinosa (North and Yoshimura, 1984) and dorsal motor nucleus of the vagus (Fukuda et al, 1987). A notable exception is the submucous plexus of the guinea pig ileum.…”
Section: Identification Of Cells Studied With Whole-cell Patch Clampmentioning
confidence: 99%
“…In addition, amphetamine, an agent that releases noradrenaline, caused a depolarization that was blocked by prazosin, indicating that the release of endogenous noradrenaline increased the excitability of dorsal raphe neurons (Pan & Williams, 1989). The most commonly reported ionic mechanism that mediates the depolarization induced by a1-adrenoceptor activation is a decrease in potassium conductance (Yoshimura et al 1985;Fukuda, Minami, Nabekura & Oomura, 1987;Freedman & Aghajanian, 1987;McCormick & Prince, 1988; Legendre, Dupouy & Vincent, 1988;McCormick, 1992;Larkman & Kelly, 1992). There are several additional reports of noradrenaline acting on various conductances, ranging from an inhibition of the transient potassium conductance (Aghajanian, 1985;Wang, Wettwer, Gross & Ravens, 1991) to both augmentation (Freedman & Aghajanian, 1987) and depression.…”
mentioning
confidence: 99%